Brand Trust as a Mediator of Digital Marketing Effects on Travel Service Purchase Decisions in Batam - Maryanti Maryanti; Bambang Satriawan; Nolla Puspita Dewi (Penerbit Goodwood, 2026)
Purpose: This study examines the effects of social media advertising, influencer marketing, website quality, and Electronic Word of Mouth (e-WOM) on travel-service purchase decisions, with brand trust as a mediator.Methodology: An explanatory survey was conducted among 150 users of 18 travel agencies in Batam, Indonesia, selected through proportional allocation and purposive screening based on prior service use and digital-channel exposure. Data were collected using Likert scales and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.1. Results: All four digital marketing dimensions positively and significantly affected brand trust. Advertising and influencer marketing also had significant direct effects on purchase decisions, while website quality and e-WOM did not. Brand trust was the strongest direct predictor of purchase decisions (? = 0.539) and mediated all four relationships, complementarily for advertising and influencer marketing and indirectly for website quality and e-WOM. The model explained 72.3% of the variance in brand trust and 72.9% in purchase decisions.Conclusions: Digital touchpoints operate through different conversion mechanisms. Paid and endorsed channels influence purchases directly, whereas owned and earned channels primarily build trust before purchase.Limitations: The cross-sectional design, self-reported data, single-city setting, and exclusion of situational or behavioral data limit generalizability.Contributions: This study integrates four heterogeneous digital touchpoints, namely paid, endorsed, owned, and earned media, within one mediation framework, demonstrating differences in both effect size and mediation type.